2011
DOI: 10.1074/jbc.m111.268466
|View full text |Cite|
|
Sign up to set email alerts
|

HIV-1 Tat Protein Promotes Neuronal Dysfunction through Disruption of MicroRNAs

Abstract: Over the last decade, small noncoding RNA molecules such as microRNAs (miRNAs) have emerged as critical regulators in the expression and function of eukaryotic genomes. It has been suggested that viral infections and neurological disease outcome may also be shaped by the influence of small RNAs. This has prompted us to suggest that HIV infection alters the endogenous miRNA expression patterns, thereby contributing to neuronal deregulation and AIDS dementia. Therefore, using primary cultures and neuronal cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 79 publications
1
47
0
Order By: Relevance
“…These findings demonstrate activation of DDR signaling and represent a potential mechanism triggering and driving miR-34a upregulation. In addition, the viral protein (HIV/SIV Tat) was also shown to induce the expression of miR-34a (43-44). Therefore, it is likely that Tat protein (direct effects of viral replication) and oxidative stress induced DDR (indirect effects of viral replication) can separately or collectively upregulate miR-34a expression in the colonic epithelium and LPL compartments.…”
Section: Discussionmentioning
confidence: 99%
“…These findings demonstrate activation of DDR signaling and represent a potential mechanism triggering and driving miR-34a upregulation. In addition, the viral protein (HIV/SIV Tat) was also shown to induce the expression of miR-34a (43-44). Therefore, it is likely that Tat protein (direct effects of viral replication) and oxidative stress induced DDR (indirect effects of viral replication) can separately or collectively upregulate miR-34a expression in the colonic epithelium and LPL compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Tat is a multifunctional, viral regulatory protein that drives HIV transcription (Parada et al 1999). Tat protein is present in post-mortem brain tissue of HIV-positive individuals with HIV-associated-dementia or – encephalitis (Chang et al 2011; Hudson et al 2000; Nath et al 2000; Wesselingh et al 1993; Wiley et al 1996), and brain expression may persist despite highly active antiretroviral therapies (Agbottah et al 2006). Functional Tat protein is secreted from HIV-1 infected monocytes and glial cells to act at membrane-bound and intracellular targets, promoting cytokine production and infiltration (Nath et al 1991; Bruce-Keller et al 2001), oxidative stress (Kruman et al 1998) and neurotoxicity (Chang et al 1997; Ensoli et al 1990, 1993; Rayne et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…49,50 Specifically, 69 microRNAs had a 2-fold change or greater response to treatment in neurons and a neuronal cell line. A reanalysis of the microarray data revealed that only 1 of the 69 microRNAs was expressed above a common detection threshold setting (negative control (background) signal plus 2 standard deviations).…”
Section: Microrna-seq Alignmentmentioning
confidence: 99%